Synthesis and antiprotozoal activity of furanchalcone-quinoline, furanchalcone-chromone and furanchalcone-imidazole hybrids (2017)
We report herein the synthesis and biological activities (cytotoxicity, leishmanicidal and trypanocidal) of several furanchalcone quinoline, furanchalcone-chromone and furanchalcone-imidazole hybrids. The synthesized compounds were evaluated against amastigotes forms of L. (V) panamensis, which is the most prevalent Leishmania species in Colombia and against Trypanosoma cruzi, which is the major pathogenic species to humans. Cytotoxicity was evaluated against human U-937 macrophages. Compounds (6e, 8a-8f, 11b and 11c) were active against both L. (V) panamensis and T. cruzi with EC50 values lower than 25 μg/mL, with 8e and 8f being the most active compounds with an EC50 of 0.39 + 0.06 μg/mL (0.78 µM) and 1.15 + 0.23 μg/mL (2.16 µM) against L. (V) panamensis, respectively, and 0.33 + 0.02 μg/mL (0.66 µM) and 0.39 + 0.02 μg/mL (0.72 µM) against T. cruzi, respectively. All hybrid compounds showed better activity than the anti-leishmanial drug meglumine antimoniate. Compounds 20 and 23 showed higher activities than benznidazole, the current anti-trypanosomal drug. Although these compounds showed toxicity for mammalian U-937 cells, they still have the potential to be considered as candidates for antileishmanial or trypanocydal drug development. There is not a clear relationship between the antiprotozoal activity and the length of the alkyl linker. However, we obtained higher bioactivity when the alkyl linker has nine and twelve carbon atoms. Furanchalcone-imidazole hybrids were the most active of all compounds, showing that the imidazole salt moiety is important for their biological actions.